Group II Metabotropic Glutamate Receptors: Role in Pain Mechanisms and Pain Modulation - Mazzitelli, Mariacristina; Palazzo, Enza; Maione, Sabatino; Neugebauer, Volker (Frontiers in Molecular Neuroscience, 2018)
Glutamate is the main excitatory neurotransmitter in the nervous system and plays a critical role in nociceptive processing and pain modulation. G-protein coupled metabotropic glutamate receptors (mGluRs) are widely expressed in the central and peripheral nervous system, and they mediate neuronal excitability and synaptic transmission. Eight different mGluR subtypes have been identified so far, and are classified into Groups I-III. Group II mGluR2 and mGluR3 couple negatively to adenylyl cyclase through Gi/Go proteins, are mainly expressed presynaptically, and typically inhibit the release of neurotransmitters, including glutamate and GABA. Group II mGluRs have consistently been linked to pain modulation; they are expressed in peripheral, spinal and supraspinal elements of pain-related neural processing. Pharmacological studies have shown anti-nociceptive/analgesic effects of group II mGluR agonists in preclinical models of acute and chronic pain, although much less is known about mechanisms and sites of action for mGluR2 and mGluR3 compared to other mGluRs. The availability of orthosteric and new selective allosteric modulators acting on mGluR2 and mGluR3 has provided valuable tools for elucidating (subtype) specific contributions of these receptors to the pathophysiological mechanisms of pain and other disorders and their potential as therapeutic targets. This review focuses on the important role of group II mGluRs in the neurobiology of pain mechanisms and behavioral modulation, and discusses evidence for their therapeutic potential in pain.